Lean transformation at Global Connect - Allon, Gad (SAGE Knowledge. Cases., 2017)
Global Connect, a major telecommunications service provider, partners with national cable providers to bundle media and telecom services offered through voice over Internet protocol (VoIP). Global Connect provides the VoIP physical infrastructure that enables cable providers to offer VoIP phone service to their end customers. VoIP cable services are growing at a faster rate than anticipated, leaving Global Connect incapable of meeting contractual agreements with the cable partners and preventing them from capturing substantial VoIP market opportunities. Students are asked to improve the configuration of work at this service organization by identifying the types of waste in the current process. Process improvements use lean tools and their impact is quantified using time and capacity analysis.